Effect on Soil Properties and Crop Yields to Long-Term Application of Superabsorbent Polymer and Manure - Yang, Yonghui; Wu, Jicheng; Du, Yan-Lei; Gao, Cuimin; Tang, Darrell W. S.; van der Ploeg, Martine (Frontiers in Environmental Science, 2022)
Intensive farming leads to soil degradation, and poses a serious threat to agricultural yield sustainability and soil ecology. Superabsorbent polymer (SAP) and organic manure (OM) are amendments that can remediate the soil, and improve soil structure and soil pore characteristics, thereby enhancing soil quality and promoting crop growth. These benefits may be enhanced through long-term continuous application of the amendments. X-ray computed tomography (CT) was used to determine the number, connectivity, and locations of pores (160–1,000 μm, >1,000 µm) in the soil at depths of 0–100 cm. Soil organic carbon content, proportion of water-stable macroaggregates (>0.25 mm) (WSM), soil bulk density, field water capacity, available water content, wilting point content, and saturated hydraulic conductivity were also determined. Compared to the control, long-term SAP and OM treatments significantly increased the number of 160–1,000 µm and >1,000 µm soil pores (5–20 cm depths), >1,000 µm and >160 µm soil porosity (at 0–20 cm depths), total organic carbon (10–20 cm and 40–50 cm), field water capacity (0–20 cm), available water content (0–20 cm), wilting point (10–30 cm), saturated water content (10–70 cm), saturated hydraulic conductivity (0–90 cm), and WSM (0–30 cm and 40–50 cm) while decreasing the soil bulk density (0–70 cm). Compared to OM, SAP had greater beneficial effects on the total organic carbon, soil field water capacity, available water content, saturated water content, saturated hydraulic conductivity, and WSM in soil at 0–20 cm depth. The improvements to soil quality resulted in an increase in the yields of wheat and maize. Therefore, although SAP and OM were both effective at improving soil properties and increasing the economic yield of wheat and maize, the effectiveness of SAP was greater than that of OM.